(untitled) (Revista de Artes Marciales Asiáticas, 2012)
Physical disabilities lead to difficult challenges for many people. The teachings of Siddhartha Gautama, the Buddha (“Awakened One”), including the practice of mindfulness, have been described by some as a form of cognitive psychology. Mindfulness is a means of restraining our minds and reactions so that we might be relieved of suffering. The successful cultivation of mindfulness often begins with developing a healthy body, so that we might be able to meditate for significant periods of time as we cultivate mindfulness. Spiritually-minded martial arts training can provide numerous benefits for everyone, including individuals with disabilities who may seek formal and informal programs with such emphasis.